2013
DOI: 10.1523/jneurosci.3572-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Target Selectivity of Feedforward Inhibition by Striatal Fast-Spiking Interneurons

Abstract: The striatal microcircuitry consists of a vast majority of projection neurons, the medium spiny neurons (MSNs), and a small yet diverse population of interneurons. To understand how activity is orchestrated within the striatum, it is essential to unravel the functional connectivity between the different neuronal types. Fast-spiking (FS) interneurons provide feedforward inhibition to both direct and indirect pathway MSNs and are important in sculpting their output to downstream basal ganglia nuclei. FS interneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 53 publications
2
67
1
Order By: Relevance
“…However, this inhibitory blanket does not equally influence all types of neighboring neurons but rather displays selectivity in its targeting. In the striatum, PV interneurons selectively avoid cholinergic interneurons, while robustly inhibiting neighboring MSNs [28 ], thus exhibiting a high degree of selectivity in the local circuitry, similar to the local target preference found in neocortical interneurons [29] (Figure 1). …”
Section: Striatal Interneuron Connectivitymentioning
confidence: 69%
See 1 more Smart Citation
“…However, this inhibitory blanket does not equally influence all types of neighboring neurons but rather displays selectivity in its targeting. In the striatum, PV interneurons selectively avoid cholinergic interneurons, while robustly inhibiting neighboring MSNs [28 ], thus exhibiting a high degree of selectivity in the local circuitry, similar to the local target preference found in neocortical interneurons [29] (Figure 1). …”
Section: Striatal Interneuron Connectivitymentioning
confidence: 69%
“…(a) Schematic representation of an experiment showing robust inhibition of MSNs by optogenetic activation of fast-spiking PV-expressing interneurons and avoidance of a simultaneously recorded neighboring cholinergic interneuron (CHIN). (b) Blanket of feed-forward inhibition by PV interneurons onto MSNs, with 'holes' representing the avoided cholinergic interneurons.Adapted from[27,28 ].…”
mentioning
confidence: 99%
“…We injected 5 PV-Cre transgenic mice with excitatory opsin (AAV5-EF1a-DIO-C1V1(E122T/E162T)-TS-EYFP) and 4 with inhibitory opsin (AAV5-EF1a-DIO-eArch3.0-EYFP) viruses. Over 90% of the optogenetically identified neurons (92%, 39 out of 42) exhibited narrow waveforms and a wide spectrum of firing rates, indicating that indeed striatal FSIs overlap strongly with PV + neurons (Kawaguchi, 1993; Kim et al, 2016; Szydlowski et al, 2013) (Figures 3H, S4M and S4N). …”
Section: Resultsmentioning
confidence: 99%
“…Second, because of the known overlap of parvalbumin-immunoreactive (PV + ) cells and FSIs (Kawaguchi, 1993; Szydlowski et al, 2013), we used histology to analyze the number of PV + cells in control mice and chronically stressed mice immediately (n = 10 per group) or one month (n = 14 per group) after immobilization stress. The PV + cell count decreased only slightly and insignificantly at both time points (Figure 3G), suggesting that the primary stress effect was not neuronal death, but a reduction in FSI firing rates.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, despite this evidence of nicotinic stimulation and depolarizing responses to cholinergic stimulation, FSIs do not appear to play a major role in the disynaptic inhibition of SPNs through cholinergic interneurons (Nelson et al, 2014b). CIN to FSI synaptic connections are not reciprocal as it has been shown that FSI cells do not form synapses onto cholinergic interneurons (Straub et al, 2016; Szydlowski et al, 2013). …”
Section: Local Striatal Circuitrymentioning
confidence: 99%